Stock Price Volatility and Role of Dividend Policy: Empirical Evidence from Pakistan - Shah, Syed Akif; Noreen, Umara (International Journal of Economics and Financial Issues, 2016)
Despite years of empirical research, the linkage between dividend policy and stock price volatility remains controversial among the researchers and scholars. This research endeavors to figure out the relationship between stock price volatility and dividend policy of listed companies in Pakistan. A sample of fifty firms, based upon consistent dividend paying behavior, listed on Karachi Stock Exchange has been selected from non-financial sectors, for the period of 2005 to 2012. Multiple regressions analyses have been carried on by applying random effect model on panel data i.e. for empirical estimation and robustness, panel EGLS methods is used for finding relationship between dividend policy (dividend payout and dividend yield) and stock price volatility after controlling for firm size, asset growth, long term debt, earning volatility and earnings per share. The study has found significant negative relationship between stock price volatility and dividend policy variables i.e. dividend payout and dividend yield. Study has also found significant positive relationship between control variables (asset growth, earning volatility and earnings per share) and stock price volatility in KSE. But in case of the remaining two control variables i.e. firm size and long term debt, these were found to be negatively related to stock price volatility. The findings of this research are expected to contribute to dividend policy literature by providing evidence from Pakistani stock market to prior studies done in developed and developing countries. Keywords: Stock Price Volatility, Dividend Policy, Dividend Yield, Dividend Payout, Karachi Stock Exchange (KSE), Random Effect Model. JEL Classifications: G20. G30, G35